2013
DOI: 10.1209/0295-5075/101/17008
|View full text |Cite
|
Sign up to set email alerts
|

Spin-phonon coupling in multiferroic RCrO 3 (R-Y, Lu, Gd, Eu, Sm): A Raman study

Abstract: -Raman study on a select few orthochromites, RCrO 3 (R = Y, Lu, Gd, Eu and Sm) shows that the phonon behavior at T N in compounds with magnetic R-ion (Gd and Sm) is remarkably different from that of non-magnetic R-ion (Y, Lu and Eu). While anomalies in most of the observed phonon frequencies in all these compounds may result from the distortion of CrO 6 octahedra due to size effect and magnetostriction arising from Cr-ordering, the anomalous behavior of their linewidths observed at T N for the compounds with o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
88
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 41 publications
18
88
0
Order By: Relevance
“…The dotted lines represent the fitted curves for anharmonic contributions to these modes according to Eq. 27 . This suggests the presence of spin-phonon coupling due to magnetic interaction between Gd 3+ and Cr 3+ moments which is mediated by the weak ferromagnetic coupling (canted) of Cr-sublattice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dotted lines represent the fitted curves for anharmonic contributions to these modes according to Eq. 27 . This suggests the presence of spin-phonon coupling due to magnetic interaction between Gd 3+ and Cr 3+ moments which is mediated by the weak ferromagnetic coupling (canted) of Cr-sublattice.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Raman studies show anomalous change of phonon frequency and a decrease in phonon life times across the mutiferroic transition temperature, both in the modes involving CrO 6 octahedra and magnetic R-ion 27 . This suggests that ferroelectricity in RCrO 3 is driven by magnetostriction mechanism caused by 3d-4f coupling, resulting in the displacement of the R-ion and the octahedral distortion via oxygen displacements.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been shown that RS is also an appropriate probe for the investigation of lattice distortions and slight changes in octahedra rotations [15][16][17][18]. Further to this, RS is an ideal probe for the investigation of spinphonon coupling phenomena [19][20][21][22][23]. Finally, RS is a now widely used technique for probing even subtle straininduced structural modifications in oxide thin films [24][25][26].…”
Section: +mentioning
confidence: 99%
“…In the first magnetic transition at 1~ 90 K the anomalies are due to the coupling directly between the magnetic ordering and lattice (phonon) since CMO does not show any anomaly in the lattice parameters in this magnetic transition 23 , what discards the possibility of the coupling be due to the magnetostriction effect 27 . However, the second spin-phonon coupling anomaly at 2~ 50 K could be due to magnetostriction effect, as once at this magnetic transition the lattice parameters of CMO change significantly.…”
mentioning
confidence: 90%